Opportunities for rhinovirus-targeted RNA therapeutics: A narrative review - Camille Esneau; Nathan E Bryant; Sebastian L Johnston; Nathan W Bartlett (CMI Communications)
Background: Rhinoviruses (RVs), first identified as common causative agents of the common cold, are now recognised as significant contributors to exacerbations of chronic respiratory diseases (asthma, chronic obstructive pulmonary disease, cystic fibrosis), and severe lower respiratory tract infections in infants, the elderly and the immunocompromised. Despite their significant impact, no RV vaccines or RV-specific antivirals have been approved for use, largely due to the viruses’ extensive antigenic diversity and limited antibody cross-reactivity across the ∼180 RV subtypes. This complexity has long hindered traditional therapeutic approaches. By enabling rapid adaptation to viral diversity and targeting previously non-targetable but highly conserved regions of the viral genome, RNA-based technologies offer promising new approaches to overcome these challenges. Objectives: This narrative review provides an update on RV virology and epidemiology, an overview of attempts to develop treatments for RV, and describes recent advances in RNA therapeutics in the prevention and treatment of other viral pathogens that could be adapted for use against RVs. Sources: This narrative review was conducted through a comprehensive literature search using PubMed® and Web of Science™ with search terms related to the development of RNA therapeutics for respiratory viruses and picornaviruses. The methodology is further defined in the body of the text. Content and implications: Recent developments in RNA therapeutics for similar respiratory viruses and related RNA viruses have shown promise, both in preventing infection through mRNA vaccination and treating infections with various RNA-based antivirals. Developing effective RV-targeting therapeutics is imperative to reduce both the clinical and economic burden of RV infections.